Care demands experienced by family caregivers of children with Primary Immunodeficiency - Milka Gabrielle de Lira Nóbrega West; Maria Gorete Lucena de Vasconcelos; Maria Wanderleya de Lavor Coriolano-Marinus; Ednaldo Cavalcante de Araújo (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to understand the experiences of family caregivers of children with Primary Immunodeficiency in view of care demands. Methods: a qualitative research. Data collection was subsidized by an open interview with five family caregivers, and the data were analyzed using the Bardin Content Analysis technique, thematic modality. The Callista Roy's Adaptation Model of Nursing was used to interpret the data. Results: from participants' reports, the following categories emerged: Maternity: facing adversity; Remodeling of daily life; The Social Support Network resource. Final considerations: family caregivers experience several feelings such as anguish and low self-esteem due to the fear of losing their child and the routine of illnesses and hospitalizations, in addition to needs that are often not reached due to incompatibility with the family budget. The Social Support Network is strengthened for most caregivers, playing an essential role as a coping strategy for caregivers.